Scanning Electron Microscopy for Nanostructure Analysis of Hybrid Multilayer Coating - Debi Rianto (Department of Physics – Universitas Negeri Padang UNP, 2022)
Scanning Electron Microscope (SEM) has been used in various studies to retrieve detailed information on nanomaterial structure. This study is an effort to propose SEM as the proper tool to investigate the properties of Hybrid Multilayer Coating as our model. The analysis should include nanoparticle size and its distribution on the surface, the thickness of the layers, the chemical composition and the crystal grain size in the layers. Several methods in SEM are beneficial to characterize these features are topography image, compositional image, X-Ray Spectrometry and Electron Backscattered Diffraction pattern. This technique also has several limitations ranging from chemical sensitivity, resolution to sample preparation